Sexagem cirúrgica em aves silvestres - Raso, T. F. [UNESP]; Werther, K. [UNESP] (My University, 2004)
The laparoscopy was used for sexing 349 Brazilian and exotic birds, belonging to 61 species, of 11 families and six orders. The age of the birds ranged from four months to 42 years and the body weight from 55g to 3.4kg. With this technique it was possible to visualize the gonads, evaluate their development and observe the adjacent organs. The surgical technique using a rigid endoscope for determination of sex was considered fast and safe. No death during or as a consequence of the surgical procedure was observed.
Surgical sexing in birds
Keywords: Birds; Laparoscopy; Surgical sexing